2000
DOI: 10.1002/(sici)1097-0223(200002)20:2<103::aid-pd761>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Common trisomy mosaicism diagnosed in amniocytes involving chromosomes 13, 18, 20 and 21: karyotype-phenotype correlations

Abstract: Karyotype-phenotype correlations of common trisomy mosaicism prenatally diagnosed via amniocentesis was reviewed in 305 new cases from a collaboration of North American cytogenetic laboratories. Abnormal outcome was noted in 10/25 (40%) cases of 47,+13/46, 17/31 (54%) cases of 47,+18/46, 10/152 (6.5%) cases of 47,+20/46, and in 49/97 (50%) cases of 47,+21/46 mosaicism. Risk of abnormal outcome in pregnancies with less than 50% trisomic cells and greater than 50% trisomic cells were: 26% (4/15) versus 60% (6/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 9 publications
2
37
0
Order By: Relevance
“…Chromosome-specific differences in the frequency of prenatally diagnosed autosomal mosaicism have been identified, with trisomies involving chromosomes 13, 18, 20, and 21 being seen most frequently in amniocytes [ 24,25 ].…”
Section: Constitutional Autosomal Aneuploidymentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome-specific differences in the frequency of prenatally diagnosed autosomal mosaicism have been identified, with trisomies involving chromosomes 13, 18, 20, and 21 being seen most frequently in amniocytes [ 24,25 ].…”
Section: Constitutional Autosomal Aneuploidymentioning
confidence: 99%
“…As a result of this phenotypic overlap, the term “general chromosomal mosaic syndrome” has been coined [ 35 ]. However, for a subset of these conditions, specific syndromic patterns have emerged (summarized in Table 2 [ 4,16,21,23-25,33-75 ]), thereby facilitating the recognition of the chromosomal basis for these individual's health/developmental problems. The provision of genetic counseling following a prenatal diagnosis of autosomal mosaicism can be especially challenging.…”
Section: Constitutional Autosomal Aneuploidymentioning
confidence: 99%
“…For the prenatal 14 allowing them to predict with greater confidence the potential outcome for the virtual patient. We discussed two cases in each 2-hour session.…”
Section: In-class Discussionmentioning
confidence: 97%
“…This karyotype is rarely detected in peripheral lymphocytes. A study comprising 152 cases of patients with trisomy 20 mosaicism found, through amniocentesis, an abnormal outcome in six live-born patients: one with facial dysmorphism and developmental delay, one with structural brain abnormalities and seizures, and four with intrauterine growth retardation [7]. In a study of 103 cases from 102 pregnancies diagnosed as trisomy 20 mosaicism through amniocentesis, 75 pregnancies (one carried twins) were continued, 26 terminated, and one spontaneously aborted.…”
Section: Discussionmentioning
confidence: 99%